Caribbean - Agricultural trade policy debates and developments: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
In the face of rising food prices, preference erosion and stricter standards in export markets, Caribbean governments have been seeking to promote local food production for domestic and regional markets. Those efforts have been oriented not only to an import substitution strategy (as it is the case for instance of rice, beef, maize and horticultural products) but also to reorienting traditional export sectors such as sugar and bananas to serve local and regional value-added processing industries. This Executive Brief focuses on 2012-13 policy development in the Caribbean and on the recent developments in Caribbean-EU and Caribbean-USA/Canada trade relations. It further explores the main policy debates and issues emerging as part of international negotiations and regional cooperation initiatives.